Site observations of weathered granitic soils subjected to cementation and partial drainage using SCPTU - Xianwei Zhang; Xinyu Liu; Ran An; Xinming Li (Journal of Rock Mechanics and Geotechnical Engineering, 2023)
Because of the cementation inherited from the parent rock, weathered granitic soil is usually susceptible to disturbance, which poses considerable challenges for laboratory characterization. The cone penetration test with pore pressure measurements has long been known for its reliability in site investigations and stratigraphic profiling. However, although extensive piezocone test results and experience are available for sedimentary soil, similar advances are yet to be made for weathered granitic soil. Moreover, the experience from sedimentary soil may not be directly applicable to weathered profiles because of the essentially different natures of the two types of geomaterials. This study performs seismic piezocone tests in a weathered granitic profile comprising residual granitic soil, completely weathered granite, and highly weathered granite. Pore pressure is measured at both the cone mid-face and the shoulder, and the effects of penetrometer size and penetration rate are considered. A series of updated soil behavior type charts is proposed to interpret the test results, thereby allowing the effect of weathering to be evaluated. This paper offers an important extension to the sparse data on the in situ responses of weathered materials.